(untitled) (Editora Impacto Científico, 2025)
This article examines the factors influencing the decision of public bodies to migrate to Brazil’s free energy market, highlighting technical, economic, regulatory, and institutional aspects. It begins by discussing the context of power sector modernization and the evolution of the free market as an alternative to the traditional regulated model, emphasizing potential cost reductions and greater contractual flexibility. Next, the bibliographic research methodology is presented, involving a review of specialized literature, official documents, and reports on international experiences, which enables a deep understanding of the dynamics involved. Using a qualitative approach, the main advantages of migration are identified, such as the ability to negotiate prices directly, budgetary predictability, and the encouragement of renewable energy adoption. Conversely, challenges related to regulatory instability, the need for specialized technical management, and administrative complexity—including specific metering, telemetry, and multiple billing—are highlighted. The pivotal role of a clear and stable normative framework capable of balancing negotiation freedom with consumer protection, especially for smaller and residential users, is also underscored. The article further examines the importance of digitalization and technological innovation through online trading platforms, smart grids, and artificial intelligence tools, which offer greater consumption control and demand forecasting. The analysis also addresses the social impact of migration, considering transparency, social oversight, and the potential reinvestment of savings into public service improvements and environmental policies. In conclusion, the need for interinstitutional coordination, ongoing training for energy managers, development of performance indicators, and innovative financial mechanisms to facilitate access to the free market is emphasized. Finally, it stresses that a successful migration requires an integrated ecosystem of governance, innovation, and monitoring, capable of consolidating energy efficiency, sustainability, and social justice within the public sector.